Challenges in implementing clinical liquid chromatography–tandem mass spectrometry methods – seeing the light at the end of the tunnel. (18th June 2013) - Clarke, William; Rhea, Jeanne M.; Molinaro, Ross
<x xml:space="preserve">Abstract</x> The use of liquid chromatography–tandem mass spectrometry (LC–MS/MS) in the clinical setting is a relatively new application. One of the significant barriers hampering the transition of LC–MS/MS from the research lab into a clinical setting is the uncertainty of how to successfully develop and validate a method that meets guidelines for clinical applications. Here, we have taken this seemingly overwhelming process and broken it into five general stages for consideration: assessing the clinical validity of a new LC–MS/MS assay, determination of feasibility, assay development, assay validation and post‐implementation monitoring. Although various publications are available and serve as resources for determining development processes and acceptability criteria for specific LC–MS/MS assays, many of them are general recommendations or are specific to research applications that may not translate either practically or clinically. In this perspective special feature article, a resource is compiled that describes key differences between LC–MS/MS methods for research use versus clinical use. In addition, the challenges facing the expanding role of this technique in the clinical setting are discussed, including instrumentation/automation challenges, potential regulation of laboratory developed tests by the US Food and Drug Administration and standardization and harmonization of MS methods through the use of traceable materials and availability of guidance documents. Copyright © 2013 John Wiley & Sons, Ltd.